Bioactive Profile and Health Benefits of Wedang Uwuh: A Narrative Mini-Review - Darmawan, Rahmad; Primartati, Danny Meganingdyah; Puspa Dila Rohmaniar (LPPM, Universitas Muhammadiyah Riau, 2026)
Background: Wedang uwuh is a traditional Indonesian herbal drink made from ginger, sappan wood, clove leaves, nutmeg leaves, rock sugar, and several other spices, and it is known for its health benefits. Objective: This review aims to summarize scientific evidence on the bioactive compounds, biological activities, and health potential of wedang uwuh. Methods: Literature was reviewed from scientific articles discussing the phytochemical composition and pharmacological activities of wedang uwuh. Results: The findings show that wedang uwuh contains polyphenols, flavonoids, gingerol, shogaol, and other bioactive metabolites with antioxidant, anti-inflammatory, and antidiabetic activities, and may also support weight management. Conclusion: Wedang uwuh has potential as a functional drink that supports health and represents part of Indonesia’s cultural heritage, although further studies, including toxicity tests and clinical research, are still needed to confirm its safety and effectiveness.